Faktor - Faktor yang Mempengaruhi Keputusan Menggunakan Jasa Bank Syariah di PT. BSI Kota Batu - Ahmad Ramapanji Panatagama; Irmayanti Hasan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the factors that influence the decision to use sharia banking services at PT. BSI Batu City. This research uses a descriptive quantitative approach with questionnaire and interview data collection methods. The population in this study were customers at PT. BSI Batu City and samples as research respondents will be taken using non-probability sampling techniques using Malhotra's theory using 105 samples obtained from 5 x 21 (number of items from research indicators). The research results show that the level of religiosity (X1) and level of education (X3) have a significant and positive effect on usage decisions. Meanwhile, income level (X2) has no effect and is not significant on the decision to use sharia banking services at PT. BSI Batu City.